Observations on the mechanism of salicylate-induced antipyresis - Cranston, W. I. (1970)
1. Fever has been produced in conscious rabbits, first, by injection of leucocyte pyrogen into the lateral cerebral ventricle and, second, by local cooling of the hypothalamus. 2. Both intravenous and intraventricular salicylate produce antipyresis during an established fever due to intraventricular leucocyte pyrogen. This is incompatible with the hypothesis that salicylate acts by interfering with the passage of leucocyte pyrogen from the circulation into the hypothalamus. 3. Intravenous sodium salicylate has no effect on the fever due to local cooling of the hypothalamus. This suggests that salicylates do not act on central or peripheral efferent pathways involved in thermoregulation.